(3GdhShSI (B:s (3QDjI TQYjI hWHjI hOQGSI ejOGfjI (B/s - (3GdYhGO,YHO GdQMef Hf SGjQs; (3GdMeO, YHO GdQRGb eMehO jGSjfs ((3GdOeGe, GdSYhOjI (B:s (3OGQ GHf GdLhRj ddfTQ hGdJhRjY,s, 2009)
(3GdCeQGV GdfaSjI(B.s
Keywords: (3GdhShGS (B((3Yde faS(B)s